Antimaximum principle in exterior domains. (January 2016) - Anoop, T.V.; Drábek, P.; Sankar, Lakshmi; Sasi, Sarath
Abstract: We consider the antimaximum principle for the p -Laplacian in the exterior domain: − Δ p u = λ K ( x ) ∣ u ∣ p − 2 u + h ( x ) in B 1 c